Lower bone turnover markers in metabolic syndrome and diabetes: the population-based Study of Health in Pomerania - Lerchbaum, Elisabeth; Schwetz, V.; Nauck, M.; Völzke, H.; Wallaschofski, H.; Hannemann, A. (Nutrition, metabolism and cardiovascular diseases, 2015)
Accumulating evidence demonstrates an important interaction between bone and energy metabolism. We aimed to study the associations of three bone turnover markers (BTM: osteocalcin, beta-crosslaps, procollagen type 1 N-terminal propeptide) as well as of 25-hydroxyvitamin D and parathyroid hormone with metabolic syndrome (MetS) or type 2 diabetes mellitus (T2DM) in a large population-based cohort.